2007
DOI: 10.1248/bpb.30.1422
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effects of Soyo-san on Immobilization Stress in Ovariectomized Female Rats

Abstract: Depressive disorders are among the most frequently occurring psychiatric diseases, and are prevalent in at least 15% of the population. However, the prevalence of depressive disorders is twice as high in women as in men.1) The higher incidence and severity of depression is associated with the presence or absence of ovarian hormones.2) The ovarian hormones related to the menopause-induced depression influence the hippocampal anatomy and physiology; thus, they affect behavior in adult female rats. [3][4][5] The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The cholinergic system is known to be involved in the information processing related to hippocampal learning and memory, and the central cholinergic neurons are of putative relevance to major depression [23]. Learning and memory in mammals, including humans, is dependent on the neurotransmitter acetylcholine, in the basal forebrain and hippocampus [24].…”
Section: Discussionmentioning
confidence: 99%
“…The cholinergic system is known to be involved in the information processing related to hippocampal learning and memory, and the central cholinergic neurons are of putative relevance to major depression [23]. Learning and memory in mammals, including humans, is dependent on the neurotransmitter acetylcholine, in the basal forebrain and hippocampus [24].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Repeated stress causes numerous neurochemical and neuroanatomical changes in the brain, mainly in the hippocampus, including excessive activity of the hypothalamo-pituitary-adrenal (HPA) axis. 6) As a result, neurogenesis is reduced, hippocampal areas CA1 and CA3 undergo dendritic remodeling, 7,8) and neuronal atrophy occurs, leading to a decrease in neuronal volume and the total number of neurons and their branches. 9) Hippocampal neurons, which are known to play an important role in learning and memory, are particularly vulnerable to neuronal injury produced by stress-induced glucocorticoid (GC) levels, 10) resulting in deficits in spatial memory tasks, 11) and synaptic plasticity.…”
mentioning
confidence: 99%
“…It has been shown that psychological stress can induce dysfunctions in the nervous system, including cognitive impairment, anxiety, and insomnia [ 3 ]. Recent studies have shown that both intense acute and chronic stress can have detrimental neurocognitive effects [ 4 5 ], and repeated stress induces neurochemical and neuroanatomical changes in the brain, mainly in the HPA axis [ 6 ]. Memory and learning performances were also observed to decrease under chronic stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%